Revisiting the Nexus among Bank Specific Factors, Macroeconomic Factors, and Islamic Banking Performance: Three Measurement Models - Razali Razali; Slamet Haryono; Ousmane Salifou Abdou; Munawar Rizki Jailani; Imamuddin Imamuddin (Shirkah: Journal of Economics and Business, 2025)
Much of the research on Islamic banking performance relies on conventional metrics rather than Islamic metrics, warranting further exploration. This study provides an empirical analysis of bank-specific and macroeconomic factors on Islamic banking performance from 2016 to 2024 using three measurement models. Monthly data were processed using the ARDL approach and revealed that capital adequacy influences Islamic banking performance in the short term, but has no effect in the long term. Liquidity has an effect only in the long term. Financing Outstanding has a negative effect in the short and long term, while diversification has an effect in the short term but no effect in the long term. Bank size affects performance in the short term, but not in the long term, while macroeconomic factors show an inconsistent relationship. In the IPR model, inflation and exchange rates have no impact in either the short or long term. However, in the ROA and NOM models, these factors affect the long term, but not the short term. This study suggests that banks need to pay attention to financing and exchange rate risks, including the implementation of a strong risk-management system.